1998
DOI: 10.1097/00001610-199803000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Women with Gastrointestinal Symptoms: Implications for Nursing Research and Practice

Abstract: Irritable bowel syndrome and functional bowel disorder are diagnoses used to describe chronic GI symptoms for which no overt pathological condition can be identified. Symptoms are more common in women and are frequently followed in gastroenterology clinics. The purpose of this article is to provide an overview of the research linking GI symptoms and reproductive cycling and to discuss implications for practice. GIGl symptoms such as stomach pain and nausea are highest during menses compared with other cycle ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In addition, stool consistency was firmer during the luteal phase. Similar observations have been made in other studies [8][9][10][11] although one study reported no change in stool form or frequency with the menstrual cycle. 10 Furthermore, although general well being was reduced at menses, anxiety and depression remained unaltered throughout the menstrual cycle.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, stool consistency was firmer during the luteal phase. Similar observations have been made in other studies [8][9][10][11] although one study reported no change in stool form or frequency with the menstrual cycle. 10 Furthermore, although general well being was reduced at menses, anxiety and depression remained unaltered throughout the menstrual cycle.…”
Section: Discussionsupporting
confidence: 88%
“…3 5 Sex hormones may also play a role in the pathogenesis of irritable bowel syndrome (IBS). This is supported by observations that more women suffer from IBS than men, 6 7 and that premenopausal female patients often report exacerbation of their symptoms at the time of menses [8][9][10][11] and have fewer episodes of abdominal bloating than postmenopausal women. 12 Furthermore, postmenopausal women taking hormone replacement therapy (HRT) experience less bloating than those not taking HRT.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…HRT use has previously been associated with an increased risk of IBS in postmenopausal women, similar to the increased risk in younger women associated with endogenous oestrogenic activity [34]. Patterns of IBS symptoms are known to vary during the menstrual cycle [35,36], and ovarian hormones are known a Odds ratio (OR) estimates with 95% confidence intervals (CI) were adjusted by age, sex, smoking, body mass index, alcohol use and healthcare utilization using logistic regression b Current/recent use was defined as a supply of the most recent prescription lasting until the index date or ending in the previous 365 days. Past use was defined as a prescription ending more than 365 days before the index date.…”
Section: Ibs In Patients With Gerdmentioning
confidence: 90%